Evolution of contourite drifts in regions of slope failures at eastern Fram Strait - Osti, Giacomo; Waghorn, Kate Alyse; Waage, Malin; Plaza-Faverola, Andreia; Ferré, Benedicte (arktos, 2019)
Geotechnical characteristics of contouritic deposition often lead to preconditioning slope instabilities and failures along glaciated and formerly glaciated continental margins. However, internal depositional geometry is also an important factor in triggering instabilities. This work highlights the importance of the tectonic and oceanographic evolution of the Northwestern (NW) Svalbard margin in determining the buildup and the internal structure of contourite drifts and the subsequent type of slope instability. The analysis of seismic reflection data reveals that the presence of two contourite drifts on the flank of an active spreading ridge in the Fram Strait—NW Svalbard margin—in an area of extensive slope instability had a major impact on the evolution of slope failure. The presence of a slope sheeted drift (or plastered drift) led to the development of rotational/translational mass movement at water depth < 2500 ms, whereas at water depth > 2500 ms the presence of sediment waves facilitated the formation of planes of shear that led to internal deformation of the lower slope through a process of slump/creep. The well-documented high seismicity of the area might have provided the necessary energy to trigger the slope instability.